Efficacy of Concentrated Growth Factor with Autograft and Xenograft in Mandible Fractures: A Randomized Clinical Trial - Samreen Malik; Abdul Hafeez Shaikh; Tahera Ayub; Amna Rehman; Hijab Farid Khan; Arifa Haque (Journal of University College of Medicine and Dentistry)
Objective: To evaluate the efficacy of adjuvant therapy with Concentrated Growth Factor (CGF) along with xenograft and autograft in mandible fractures, in terms of bone density gain and healing over the period of 6 months.